Restoration after bush control in selected rangeland areas of semi-arid savannas in South Africa - Kellner, Klaus; Mangani, Reletile T.; Sebitloane, Tshegofatso J.K.; Chirima, Johannes G.; Meyer, Nadine; Coetzee, Hendri C.; Malan, Pieter W.; Koch, Jaco (African Biodiversity & Conservation, 2021)
Background: One of the main causes of land degradation in South Africa is bush thickening (BT) of mainly Senegalia or Vachellia species. Restoration methods are required to control BT, and to improve grass biomass production and soil conditions in South Africa.Objectives: The objectives of this study were to determine the effect of brush packing (BP) as a restoration method to increase grass biomass production, assess soil moisture after BP on different soil types, and document the perceptions of the local communities towards BP.Method: Methods included cutting the stems of woodies with a diameter of at least 10 cm at knee height by chainsaw and manual clipping after which an arborocide was applied to the stumps. A neutron probe was used to measure volumetric moisture content at two different soil depths. The grass biomass was analysed using ANOVA at a confidence level of 95%. Quantitative and qualitative approaches were used to gather information about the perceptions of local communities towards restoration in group discussions.Results: The short-term data showed that the implementation of BP as restoration method increased grass biomass production. The soil texture influenced the volumetric soil moisture. Higher soil moisture content was found in the deeper clayey soils. The local participants’ interpretation towards the restoration project was positive.Conclusion: The project increased the grazing potential and contributed to job creation to improve the well-being of the people in the community.